Modelling and simulation of complex workflow processes using multi-level Petri nets. (10th March 2009) - Flores-Badillo, Marina; Lopez-Mellado, Ernesto; Padilla-Duarte, Mayra
A method for modelling complex workflow processes using a Petri Net (PN) based multilevel formalism is proposed; it yields modular and hierarchical descriptions of the organisation (or network of organisations), the processes, resource management and user interactions. The models allow the synthesis of agent based software in which mobile agents guide the cases through the organisation units; the software can be interactively executed for simulation purposes or distributed within a computer network for implementing a workflow management system. A tool for editing and simulating the models is presented.